Advancing the social identity theory of leadership: A meta-analytic review of leader group prototypicality. (February 2021) - Steffens, Niklas K.; Munt, Katie A.; van Knippenberg, Daan; Platow, Michael J.; Haslam, S. Alexander
This research advances a social identity approach to leadership through a meta-analysis examining four novel hypotheses that clarify the nature and impact of leader group prototypicality (the extent to which a leader is perceived to embody shared social identity). A random-effects meta-analysis ( k = 128, N = 32, 834) reveals a moderate-to-large effect of prototypicality that holds across evaluative and behavioral outcomes. The effect is stronger (a) when prototypicality is conceptualized as the ideal-type rather than the average group member, (b) for stronger prototypes (indexed by group longevity), and (c) for group members in formal rather than nonformal leadership roles. The effect is not contingent on group prototypicality entailing differentiation from other (out)groups. Additionally, results provide meta-analytic evidence of widely examined key factors: follower group identification (which enhances the relationship) and leader group-serving behavior (which attenuates the relationship). Building on these findings, we outline the implications for the next wave of theoretical and empirical work.